To place : becoming a landscape - Horn, Roni, 1955- (Denver, Colorado : Ginny Williams, 2001)
"Paired photographs of hot springs near Geysir were taken between 1994 and 2000. Photographs of Úlfur were taken in Reykjavík, March, 2000."